Understanding the Rural–Rural Migration of Health Workers in Two Selected Districts of Tanzania. (22nd January 2020) - Sirili, Nathanael; Simba, Daudi
Abstract : Globally, rural–urban migration has been the focus in addressing the question of availability of health workers in rural areas. Often, the rural–rural migration of health workers, another important dimension is neglected. This study aimed to analyze the magnitude and the underlying factors for rural–rural migration of health workers in two rural districts of Tanzania. An exploratory comparative cross-sectional study adopting both quantitative and qualitative approaches was carried out in two districts of Kilwa in Lindi region, southern Tanzania, and Rombo in Kilimanjaro region, northern Tanzania. In a quantitative approach, 174 health workers (both clinicians and nonclinicians) filled in a self-administered questionnaire between August 2015 and September 2016. For the qualitative sub-study, 14 key informants that included health facilities in-charges and district health managers from the two districts were interviewed. In addition, three focus group discussions were conducted with members of the health facilities committee, in the two districts. Over 40% of health workers migrated from one workstation to another between 2011 and 2015. Close to 70% of the migrated health workers, migrated within the same districts. The proportion of health workers migrated was higher in Kilwa compared to Rombo. However, the difference was not statistically significant. The major underlying factors for migration in both districts were: Caring for the family and Unfavorable working and living conditions. In Kilwa, unlike Rombo, rejection by the community, superstitious beliefs, and lack of social services, were the other major factors underlying migration of the health workers. While addressing rural–urban migration, attention should be paid also to the rural–rural migration of health workers. Lastly, addressing the migration of health workers is a multi-dimensional issue that needs the engagement of all stakeholders within and beyond the health sector.